Peter Pan and the Horror of Becoming an Adult - M. Márquez García, Carmen (Journal of Artistic Creation and Literary Research, 2025)
Childhood and adolescence are recurring themes in literature. From the archetype of the rogue in medieval literature (i.e the Spanish novella Lazarillo de Tormes, credited with founding the picaresque, genre which was to influence Cervantes and many other European writers after him) to Charles Dickens’ or Mark Twain’s young protagonists, children are used to offer sordid portraits of social realities. Many stories, with titles such as Children's and Household Tales, edited by the Grimm brothers, include narratives of hardship, where both women (hence the term ‘household’) and young people face a future devoid of opportunities. These figures have frequently been used in literature to present a portrait of middle classes as they struggled to make a place for themselves within the rapidly changing world of Western capitalism. This paper explores one of the main topics associated to young protagonists in the novels: the confrontation of the world of children and the world of adults. I will focus on Victorian society in particular and, more specifically, in the well known work authored by Scotsman J.M. Barrie, Peter Pan. I will make use of some psychoanalytic concepts in order to focus my analysis.